Evaluating The Stability of Dyke At 740 Decline Mupane Gold Mine, Botswana - Verma , Rahul; Otsisitswe , Mmapaseka T; Tauetsile , Phenyo; Matshediso , Bonny I. (International Journal of Basic and Applied Sciences, 2025)
This work is focused on evaluating the Stability of Dolerite Dyke at 740 Decline of Mupane Gold Mine. The wire meshes used to support the Dolerite Dyke, proved to insufficient and inadequate to sustain the pressure coming from the supported Dolerite Dyke and they are always at is a risk of unexpected rock falls. The work undertook the investigation of the strength of the Dolerite Dyke, and estimation of the required mean fall out weight evaluating the and extend of failure mechanism. Discontinuity data (mainly joints) obtained through the Scanline Mapping were used to analyze the rock using the RS2 software. The rock mass classification method includes RQD, which is 29.9, RMR is 58, and Q tunneling is 0.2666. These classification methods agree that the Dolerite Dyke is of inferior quality and support is recommended as per given support guidelines. It is found that the Dolerite rock has several instability problems and needs to be addressed. To reconfirm the failure limit, depth was increased to test the stability analyses of the Dolerite Dyke. This showed that as depth was increased, the in situ stress increases, creating deformations that create instability issues. Dips software analyzed the joints sets which were discovered to weaken the rock strength which made the Dolerite Dyke susceptible to failure. From unwedge analysis we the maximum volume of key books is 25cm2. Which individually cannot activate failure. From RS2 the dyke- section experiences deformation even after support installation. Installation of 2.3 m long full column pre-tensioned resin bolts into the hanging wall and sidewalls at an angle of 90 degrees, and application of 25mm thick shotcrete to the hanging wall and sidewalls after the installation are recommended to compensate for blocky ground conditions